2003
DOI: 10.1287/orsc.14.2.149.14995
|View full text |Cite
|
Sign up to set email alerts
|

Founder-CEO Succession and the Paradox of Entrepreneurial Success

Abstract: In the last few decades, we have developed a substantial body of knowledge about CEO succession. However, except for some studies of family businesses that lack direct applicability to nonfamily CEO succession, the past studies of succession have not examined the very first succession event in a firm, when the Founder-CEO is replaced, on a largescale basis. The critical differences between later-stage succession and Founder-CEO succession include the higher level of attachment between Founder-CEOs and the firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(156 citation statements)
references
References 68 publications
7
140
1
Order By: Relevance
“…Founders often make great personal sacrifices in the pursuit of firm performance, such as taking less compensation (He, 2008) 2 or diluting their control (Wasserman, 2003). They even focus their nonfinancial resources (such as their social capital) on enhancing firm performance and survival (Fischer & Pollock, 2004;Kroll, Walters, & Le, 2007).…”
Section: Major Owners and Tmt Pay Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…Founders often make great personal sacrifices in the pursuit of firm performance, such as taking less compensation (He, 2008) 2 or diluting their control (Wasserman, 2003). They even focus their nonfinancial resources (such as their social capital) on enhancing firm performance and survival (Fischer & Pollock, 2004;Kroll, Walters, & Le, 2007).…”
Section: Major Owners and Tmt Pay Dispersionmentioning
confidence: 99%
“…A high performing firm marks founders as high performing individuals (He, 2008); this applies in particular to founders who grew their firms successfully into some of the largest publicly listed firms. Even giving up the CEO position or selling ownership can be acceptable to founders if it enables their firms to garner important resources for enhanced growth and performance (Wasserman, 2003). Not surprisingly, founders' superior R&D spending, merger and acquisition activities, and capital expenditures have been related to enhanced firm performance (Fahlenbrach, 2009;Hunter et al, 2009).…”
Section: Founder Owners: Narrow Goals and Narrow Tmt Pay Dispersionmentioning
confidence: 99%
“…Unlike founders' human capital, though, a new organization's accomplishments (e.g., releasing products or receiving awards) signal the progress that a new organization has already made in resolving the market, technology, and organizational challenges that it faced initially (Spence, 1974;Wasserman, 2003). Like both organizational status and founders' human capital, an organization's accomplishments is a positional attribute that can be used to rank an organization relative to other organizations in the same population.…”
Section: Organizational Accomplishments As a Determinantmentioning
confidence: 99%
“…First, whereas most prior research has examined initial succession from the internal perspective taking into consideration a variety of firm's characteristics including firm performance, firm size, characteristics of the particular founder, completion of new product development or new financing, ownership structure and governance characteristics (Boeker and Karichilil, 2002;Bruton et al, 2000;DeTienne and Cardon, 2012;Gedajlovic et al, 2004;Rubenson and Gupta, 1997;Wasserman, 2003) we emphasize the role of the external institutional environment and provide theoretical elaboration of how a founder-CEO's perception of the institutional environment affects the process of delegating authority to a professional CEO in an emerging market context.…”
Section: Resultsmentioning
confidence: 99%
“…Another example of an empirical study of factors influencing founder-CEO departure is presented by Wasserman (2003), who found that contingencies such as completion of product development or new financing trigger founder-CEO succession. This finding pointed to multiple "paradoxes of success" in which the founder-CEO's success in achieving critical milestones actually caused the likelihood of founder-CEO succession to rise dramatically.…”
Section: Founder-ceo Succession Researchmentioning
confidence: 99%